QURANIC RASM AND ITS RELATIONSHIP WITH INTERPRETATION AND UNDERSTANDING - B, Gunawan Edi; Mahdi, Imam; Iqbal, Moch. (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
An understanding of RASM can help to prevent errors in transcription and maintain the sanctity of the Qur’an. The aims are to explore the essence of the Qur’anic RASM and its relationship with the interpreting and understanding the holy verses. This study employs the library method of collecting, reading, recording, and analyzing, then elaborates on a deep understanding of the relevant scholarly literature from journal databases, books, and scientific articles. The study results reveal that RASM Al-Qur’an or The RASM of Utsmani is the procedure for writing the Qur’an that was established during the Ustman Bin Affan, adhering to specific rules. Some ulama that RASM Al-Qur’an is tauqifi, but the majority hold that is not tauqifi. Then, the relationship between The RASM of Utsmani and the understanding of the Qur’an lies in the fact that, in the early days of Islam, the Quranic manuscript (mushaf) did not have diacritical marks (punctuation marks) or line. This difficulty became more pronounced as the Islamic world expanded into non-Arab regions, such as Persia in the east, Africa in the south and other non-Arab areas in the west.